Associations between exposure to nutrition, WASH interventions and children’s academic performance in Ethiopia: A systematic review and meta-analysis - Adugna, Yimer Mihretie; Ayelign, Abebe; Zerfu, Taddese Alemu (Springer, 2026)
Background